Attitude towards studies, self-efficacy and self-esteem of overstaying students in UPV Miag-ao, Iloilo. - Macario, Rafel M.
The study sought to demonstrate the attitude towards studies of overstaying students and its relationship to personality related variables, self-efficacy and self-esteem and the relationship between self-efficacy and self-esteeem. The study was conducted to the 40 overstaying students of College of Arts and Sciences, UPV., Design of this study was descriptive correlational. Scales used to measure the variables in this study. These were the attitude towards studies scale which was developed by the researcehrs; The Schwarzer Self-efficacy Scale and Rosenberg Self-esteem Scale. Data were analyzed using the Soearman rank Order Correlation. Analysis showed that general attitude towards studies of UPV-CAS overstaying students was not related tyo self-efficacy and self-esteem. However, looking at the dimensions of attitude towards studies, it was found out that monitoring the exams dimension had a significant relationship with self-esteem (rs=0.330; p<0.05 alpha level). It was also found out that self-efficacy had a significant relationship with self-esteem (rs=0.473;p>0.05 alpha level).